Classifying Health Information Technology patient safety related incidents – an approach used in Wales - Warm, D.; Edwards, P. (Applied Clinical Informatics, 2012)
Interest in the field of patient safety incident reporting and analysis with respect to Health Information Technology (HIT) has been growing over recent years as the development, implementation and reliance on HIT systems becomes ever more prevalent. One of the rationales for capturing patient safety incidents is to learn from failures in the delivery of care and must form part of a feedback loop which also includes analysis; investigation and monitoring. With the advent of new technologies and organizational programs of delivery the emphasis is increasingly upon analyzing HIT incidents.This thematic review had two objectives, to test the applicability of a framework specifically designed to categorize HIT incidents and to review the Welsh incidents as communicated via the national incident reporting system in order to understand their implications for healthcare. The incidents were those reported as IT/ telecommunications failure/ overload. Incidents were searched for within a national reporting system using a standardized search strategy for incidents occurring between 1st January 2009 and 31st May 2011. 149 incident reports were identified and classified. The majority (77%) of which were machine related (technical problems) such as access problems; computer system down/too slow; display issues; and software malfunctions. A further 10% (n = 15) of incidents were down to human-computer interaction issues and 13% (n = 19) incidents, mainly telephone related, could not be classified using the framework being tested.On the basis of this review of incidents, it is recommended that the framework be expanded to include hardware malfunctions and the wrong record retrieved/missing data associated with a machine output error (as opposed to human error).In terms of the implications for clinical practice, the incidents reviewed highlighted critical issues including the access problems particularly relating to the use of mobile technologies.
Keywords: Medical informatics; Patient Safety; Risk Management; Incident Reporting; Wales